The effect of education and home safety equipment on childhood thermal injury prevention: meta-analysis and meta-regression. Issue 3 (3rd June 2009) - Kendrick, D; Smith, S; Sutton, A J; Mulvaney, C; Watson, M; Coupland, C; Mason-Jones, A
Abstract : Objective: To evaluate whether home safety education and safety equipment provision increases thermal injury prevention practices or reduces thermal injury rates and whether the effect of interventions differs by social group. Methods: Systematic review and meta-analysis using individual participant data (IPD) evaluating home safety education with or without provision of free or discounted safety equipment provided to children or young people aged 0–19 years. Main outcome measures: possession of functional smoke alarm, fitted fireguard and fire extinguisher; keeping hot drinks or food and keeping matches or lighters out of reach; having a safe hot water temperature and rate of medically attended thermal injuries. Results: Home safety interventions were effective in increasing the proportion of families with a functional smoke alarm (odds ratio (OR) 1.83, 95% CI 1.22 to 2.74) and with a safe hot tap water temperature (OR 1.35, 95% CI 1.01 to 1.80). There was some evidence they increased possession of fitted fireguards (OR 1.39, 95% CI 1.00 to 1.94), but there was a lack of evidence that interventions reduced medically attended thermal injury rates (incident rate ratio (IRR) 1.12, 95% CI 0.81 to 1.56). There was no consistent evidence that the effectiveness of interventions varied by social group. Conclusions: Home safety education, especially with the provision of safety equipment, is effective in increasing some thermal injury prevention practices, but there is insufficient evidence to show whether this also reduces injury rates.